(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The U.S. Supreme Court’s Dobbs decision is examined, highlighting the theory of constitutional interpretation chosen by justices adhering to the majority opinion of the Court and criticizing the “originalism” practiced by them with the aim of overruling the precedent on abortion. The essay then focuses on the consequences to which the repetition of such an approach is likely to lead with reference to other rights and jurisprudential precedents that have hitherto characterized U.S. democracy.